Sum

Solve the following system of equations by eliminating ‘y’ (by substitution) :

3x – y = 3

7x + 2y = 20

Advertisement Remove all ads

#### Solution

We have,

3x – y = 3 ….(1)

7x + 2y = 20 ….(2)

From equation (1), we get ;

3x – y = 3 ⇒ y = 3x – 3

Substituting the value of ‘y’ in equation (2), we get

⇒ 7x + 2 × (3x – 3) = 20

⇒ 7x + 6x – 6 = 20

⇒ 13x = 26 ⇒ x = 2

Now, substituting x = 2 in equation (1), we get;

3 × 2 – y = 3

⇒ y = 3

Hence, x = 2, y = 3

Is there an error in this question or solution?

Advertisement Remove all ads

Advertisement Remove all ads